International Migration and "the New Berlin Walls" - Salah Muhsin Jasim; Samar Hussein Oglah (مجلة كلية التربية للبنات, 2025)
The refugee crisis and the increasing of the international migration towards the developed countries represented by the European Union, the United States of America and Australia have created many problems and the reappearing walls again after 30 years since of the most famous wall collapse in the last century, i.e. the fall of Berlin Wall separating East Germany, West Germany. This research discusses the viewpoints in which different opinions support and oppose building walls by reviewing viewpoints and identifying motivations and reasons for both parties and assessing the effectiveness of border walls by analyzing concerns for illegal immigration.